Critical Appraisal of Governance and Justice: Then and Now in Nepal - Bhattarai, Lokindra Hari (Molung Educational Frontier, 2018)
Governance and justice strengthen systems in order to support security, economic, politics and socio-cultural progress in the country. Nepal since ancient period of Kirats, Lichhavis, Mallas to Shah to Rana period, to Panchayat system to republican democratic state governance and justice make our civilizations more accountable, transparent, inclusive, efficient and participative. Yet they are inadequate for reflecting development and prosperity. Nepal is the first country in the history of Asia to have made the most comprehensive code of law and justice called Manab Nyayasastra (the code of human justice). Also the first country to practice natural justice –jasko pap usko gardan (one who commits crime is liable to face the punishment). Dharma in the past was one of the method to enhance governance and justice whereas the transparency, accountability, management of human, natural, economic and financial resource and equity promote governance in the federal system in the present days. The paper aims at presenting critical appraisal of governance and justice since period of Dharmasastra to modern federal republican state. It highlights with diverse stakeholders involved in education, human rights, equity, inclusion and empowerment initiatives in federal republican state. Dharma was pillar in the past whereas equity, equality, transparency, accountability, rule of law and inclusion are grains of modern concept of governance and justice.